Poda Na Lima: Islamic Character Based on Local Wisdom in Angkola-Mandailing - Rohman Rohman; Rica Umrina Lubis (Institut Agama Islam Negeri Bengkulu, 2020)
Poda Na Lima is Angkola-Mandailing local wisdom means five advices which are used as a basis for the formation of islamic character of its people in their life. This local wisdom has dealt with islam such as to maintain cleanliness and purity both mentally and physically. This study explains about how Islamic character based on “Poda Na lima” local wisdom in Angkola-Mandailing community. The five basic values of Poda Na Lima are paias rohamu (the obligation to purify your hearth), paias pamatangmu (the obligation to purify your body), paias parabitonmu (the obligation to clean your clothes), paias bagasmu (the obligation to clean your house) and paias pakaranganmu (the obligation to clean the environment). This type of research was qualitative using a qualitative descriptive approach. Data collection techniques are done by observation, in-depth interviews and literature review that examines directly about Poda Na Lima. Data analysis used systematically starting from data collection, data presentation, data reduction to draw conclusions. The result of this study shows that those traditions were very important identities to of Angkola-Mandailing community particularly to perform a good character and personalities to build a clean and healthy community order. And also become a guideline and foundation of life held by every Angkola-Mandailing ethnic group in managing life.